High-resolution Sequence Stratigraphy, Facies Analysis, and Sediment Quantification of the Cretaceous Gallup System, New Mexico, U.S.A. - Lin, Wen (My University, 2018)
The quantification of sediment budget in a well-defined ancient source-to-sink (S2S) system is vital to understand Earth history and basin evolution. Fulcrum analysis is an effective approach to estimate sediment volumes of depositional systems, given total mass balance throughout source areas to basins. The key to this approach is to quantify sediment in a closed S2S system with time controls. We analyzed Allomember E of the Cretaceous Dunvegan Alloformation in the Western Canadian Sedimentary Basin to test this sediment estimation approach. The results indicate that the sediment transported by the trunk-river generically matches the sediment estimated to be deposited in the basin. The upper-range estimate may suggest mud dispersal southward by geostrophic currents. Deciphering the relationships between traditional lithostratigraphy and sequence stratigraphy is the key to correctly understanding time-stratigraphic relationships. High-resolution sequence stratigraphic analysis of the Cretaceous Gallup system documents the high-frequency depositional cyclicity using detailed facies analysis in extensively exposed outcrops in northwestern New Mexico, US. We identified thirteen stratigraphic sequences, consisting of twenty-six parasequence and sixty-one parasequences. Shoreline trajectories are evaluated based on the geometry of the parasequences. The results show the previously identified sandstone tongues are equivalent to high-frequency sequence sets. The depositional duration estimates of respective sequence stratigraphic units, associated with the estimated changes in relative sea level, imply that Milankovitch-cycle-dominated glacio-eustasy may be the predominant control on the high-frequency sequence stratigraphy. Shoreline processes are more dynamic and complicated with mixed-energy dominance. The re-evaluation of the depositional environments of the Gallup system and the reconstructions of the paleogeography with temporal controls help to examine the depositional evolution in space and time. Paleogeographic reconstructions at parasequence scales allow for the documentation of the process-based lateral facies variations and the depositional evolution. The distinction between different wave-dominated facies associations is proposed based on this process-based facies analysis.
Keywords: Sequence Stratigraphy; Facies Analysis; High-Resolution; Sediment Quantification; Gallup